Exploiting Energy- Aware Localization with Social Network Based Interaction in Mobile Phones - Vipin, Ambat; Uma, S; Subin, PS; Sankar, KV (International Journal of Computer Sciences and Engineering, 2015)
Observational research on the social impact of cell phone usage in public places suggests that the mere presence of cell phones in public conflicts the private and public spheres and inhibits social interaction with proximate others,saving the energy of the mobile phones , storage of user profile data and make sharing quickly becomes difficult. In addition to mobility, another defining characteristic of mobile systems is user social interaction. To manage this entire problem two methods have been proposed, initially E-Shadow method is proposed for distribute mobile local social networking system. E-Shadow has two main components: (1) Local profiles. They enable E-Shadow users to record and share their names, interests, and other information with fine-grained privacy controls. (2) Mobile phone based local social interaction tools. E-Shadow provides mobile phone software that enables rich social interactions. In second design and prototype an adaptive location service for mobile devices, a-Loc, that helps reduce this battery drain. The proposed design is based on the observation that the required location accuracy varies with location, and hence lower energy and lower accuracy localization methods. It continuously tune continually tunes the energy expenditure to meet the changing accuracy requirements using the available sensors. A Bayesian estimation framework is used to model user location and sensor errors. Experiments on real world Windows Mobile phones and large-scale simulations show that our system disseminates information efficiently; it helps receivers find the direction of a specific location with accuracy. The experiments demonstrate that can recognize not only whether a social interaction is taking place, but also the type of social interaction, distinguishing between formal and informal user social settings.Focusing on helping behaviour in particular, Results Indicate That While On The Cell Phone, Users Are Less Likely To Offer Help.